Acupuncture for acute non-specific low back pain: a protocol for a randomised, controlled multicentre intervention study in general practice—the Acuback Study. Issue 3 (25th June 2012) - Skonnord, Trygve; Skjeie, Holgeir; Brekke, Mette; Grotle, Margreth; Lund, Iréne; Fetveit, Arne
Abstract : Introduction: Some general practitioners (GPs) treat acute low back pain (LBP) with acupuncture, despite lacking evidence of its effectiveness for this condition. The aim of this study was to evaluate whether a single treatment session with acupuncture can reduce time to recovery when applied in addition to standard LBP treatment according to the Norwegian national guidelines. Analyses of prognostic factors for recovery and cost-effectiveness will also be carried out. Methods and analysis: In this randomised, controlled multicentre study in general practice in Southern Norway, 270 patients will be allocated into one of two treatment groups, using a web-based application based on block randomisation. Outcome assessor will be blinded for group allocation of the patients. The control group will receive standard treatment, while the intervention group will receive standard treatment plus acupuncture treatment. There will be different GPs treating the two groups, and both groups will just have one consultation. Adults who consult their GP because of acute LBP will be included. Patients with nerve root affection, 'red flags', pregnancy, previous sick leave more than 14 days and disability pension will be excluded. The primary outcome of the study is the median time to recovery (in days). The secondary outcomes are rated global improvement, back-specific functional status, sick leave, medication, GP visits and side effects. A pilot study will be conducted. Ethics and dissemination: Participation is based on informed written consent. The authors will apply for an ethical approval from the Regional Committee for Medical and Health Research Ethics when the study protocol is published. Results from this study, positive or negative, will be disseminated in scientific medical journals. Trial Registration Number: ClinicalTrials.gov Identifier: NCT01439412 .